Guideline for Reversal of Antithrombotics in Intracranial Hemorrhage - Frontera, Jennifer A; Lewin III, John J; Rabinstein, Alejandro A; Aisiku, Imo P; Alexandrov, Anne W; Cook, Aaron M; del Zoppo, Gregory J; Kumar, Monisha A; Peerschke, Ellinor I. B; Stiefel, Michael F; Teitelbaum, Jeanne S; Wartenberg, Katja E; et al. (Neurocritical care, 2016)
BackgroundThe use of antithrombotic agents, including anticoagulants, antiplatelet agents, and thrombolytics has increased over the last decade and is expected to continue to rise. Although antithrombotic-associated intracranial hemorrhage can be devastating, rapid reversal of coagulopathy may help limit hematoma expansion and improve outcomes.MethodsThe Neurocritical Care Society, in conjunction with the Society of Critical Care Medicine, organized an international, multi-institutional committee with expertise in neurocritical care, neurology, neurosurgery, stroke, hematology, hemato-pathology, emergency medicine, pharmacy, nursing, and guideline development to evaluate the literature and develop an evidence-based practice guideline. Formalized literature searches were conducted, and studies meeting the criteria established by the committee were evaluated.ResultsUtilizing the GRADE methodology, the committee developed recommendations for reversal of vitamin K antagonists, direct factor Xa antagonists, direct thrombin inhibitors, unfractionated heparin, low-molecular weight heparin, heparinoids, pentasaccharides, thrombolytics, and antiplatelet agents in the setting of intracranial hemorrhage.ConclusionsThis guideline provides timely, evidence-based reversal strategies to assist practitioners in the care of patients with antithrombotic-associated intracranial hemorrhage.